Language and Power: A Critical Discourse Analysis of Wole Soyinka’s The Lion and the Jewel - Goodseed, Ochulor Nwaugo (Journal of English Language and Literature (ISSN: 2368-2132), 2018)
The play, The Lion and the Jewel by Soyinka has been projected variously as a triumph of African culture over the Western culture. This is because it is a post-colonial write-up that came almost after the end of the struggles that got Nigeria its independence. There have been different approaches to the study of this text with respect to the struggles between the two traditions as represented by Lakunle (the Western tradition) and Baroka (the African tradition). However, this paper takes a different dimension. Its concern is to investigate, using Fairclough’s tools of Critical Discourse Analysis, some of the ideologies and power relations embedded in some discourses in the text which reveal, in the same context, that Yoruba (African) traditional marriage ideology of bride price oppresses and marginalizes women whereas Western marriage ideology empowers and helps women to discover their self-worth. In addition too, the play reveals that chauvinism in African man cannot be completely eroded no matter the level of Western education acquired. In other words, there were still other levels of imperialism within the so called “independent world” of the traditional Yoruba and at large, Africa.